Licnostnye kacestva kak osnova rezul'tativnosti prygunov v vodu vysokogo klassa - Raspopova E.A. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2014)
The article presents the data of experimental studies of personal characteristics of divers of high class versus less successful athletes. The study of a personality was conducted by widely known methods in psychology: diagnosis of accentuation of personality (Shmishek`s technique) and R. Cattell`s 16-faktor technique.